2007
DOI: 10.1098/rspb.2007.0884
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen evolution and disease emergence in carnivores

Abstract: Emerging infectious diseases constitute some of the most pressing problems for both human and domestic animal health, and biodiversity conservation. Currently it is not clear whether the removal of past constraints on geographical distribution and transmission possibilities for pathogens alone are sufficient to give rise to novel host-pathogen combinations, or whether pathogen evolution is also generally required for establishment in novel hosts. Canine distemper virus (CDV) is a morbillivirus that is prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
166
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(182 citation statements)
references
References 69 publications
14
166
1
1
Order By: Relevance
“…The signaling lymphocyte activation molecule has long been proposed as a morbillivirus receptor (Tatsuo et al, 2001), and although exact virus:receptor interactions are unknown, it is now generally accepted that multiple receptors are utilized by these viruses (Fujita et al, 2007) and that this must have a significant effect on the potential for species-to-species transmission (von Messling et al, 2001). For CDV, it has been demonstrated that molecular adaptation at specific receptor-binding sites of the H gene is associated with the spread of this virus from dogs to novel noncanid hosts in the wild (McCarthy et al, 2007). It is possible that the Cape fur seals lack the necessary receptors to enable infection with the Namibian CDV strain, as it is known that different seal species vary in their susceptibility to PDV (Hall, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The signaling lymphocyte activation molecule has long been proposed as a morbillivirus receptor (Tatsuo et al, 2001), and although exact virus:receptor interactions are unknown, it is now generally accepted that multiple receptors are utilized by these viruses (Fujita et al, 2007) and that this must have a significant effect on the potential for species-to-species transmission (von Messling et al, 2001). For CDV, it has been demonstrated that molecular adaptation at specific receptor-binding sites of the H gene is associated with the spread of this virus from dogs to novel noncanid hosts in the wild (McCarthy et al, 2007). It is possible that the Cape fur seals lack the necessary receptors to enable infection with the Namibian CDV strain, as it is known that different seal species vary in their susceptibility to PDV (Hall, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The previously described eight lineages of CDV (McCARTHY; SHAW; GOODMAN, 2007;WOMA et al, 2010) were clearly characterized when the strains were compared. The strains of CDV from Brazil seemed to form a distinct cluster, but one strain (EU098102) was distant from the others, suggesting that there might be two strains of CDV circulating within northern Paraná.…”
Section: Etiology and Viral Propertiesmentioning
confidence: 99%
“…There is approximately 10% variation in the amino acid sequences of the H protein, with biological effects on the virus-host reactions (KAPIL et al, 2008), and since it is one of the most variable morbillivirus proteins (PARDO; JOHNSON; KLEIBOEKER, 2005), has been extensively used to evaluate phylogenetic relationships of CDV lineages worldwide (PARDO; JOHNSON; KLEIBOEKER, 2005;McCARTHY;SHAW;GOODMAN, 2007;KAPIL et al, 2008;WOMA et al, 2010). Further, an adequate immune response by the host to this hemagglutinin protein might prevent infection (MARTELLA; ELIA; BUONAVOGLIA, 2008).…”
Section: Etiology and Viral Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…CDV affects animals, such as dogs and other carnivorous mammals (26). CDV is a single-stranded RNA virus in the paramyxovirus family.…”
Section: Canine Distemper Virus (Cdv)mentioning
confidence: 99%